2018
DOI: 10.1177/1129729818762991
|View full text |Cite
|
Sign up to set email alerts
|

Thigh arteriovenous grafts. Quantitative comparison with alternative options: A meta-analysis

Abstract: Thigh arteriovenous grafts are required in a number of patients with exhausted upper extremity veins and comprise 1%-5% of the total access procedures performed. Alternative autogenous lower extremity options are the rarely used sapheno-tibial arteriovenous fistulae, the saphenous vein transpositions, and the femoral vein transpositions. The latter have proven to be the most durable lower limb access procedures, with low infection rates and their primary patency rates ranged from 74% up to 87% at 2 years. Synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
(80 reference statements)
1
11
0
1
Order By: Relevance
“…5 This finding was further confirmed by a review that reported an average weighted infection rate of 22.9% in thigh AVGs. 33 A retrospective study that compared thigh AVGs and HeRO grafts reported similar findings for infection (29% for thigh AVGs vs 15% for HeRO grafts; P ¼ .33). 30 One single-institution study comparing outcomes of 43 thigh AVGs and 33 HeRO grafts showed similar infection rates between the two accesses (26% for thigh AVG vs 21% for HeRO graft; P ¼ .79).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…5 This finding was further confirmed by a review that reported an average weighted infection rate of 22.9% in thigh AVGs. 33 A retrospective study that compared thigh AVGs and HeRO grafts reported similar findings for infection (29% for thigh AVGs vs 15% for HeRO grafts; P ¼ .33). 30 One single-institution study comparing outcomes of 43 thigh AVGs and 33 HeRO grafts showed similar infection rates between the two accesses (26% for thigh AVG vs 21% for HeRO graft; P ¼ .79).…”
Section: Discussionmentioning
confidence: 68%
“…32 A review of 920 thigh AVGs showed a weighted secondary patency of 70.2% at 1 year and 60.8% at 2 years. 33 A retrospective analysis of FVT and HeRO grafts showed that FVT had a significantly higher 1-year primary patency (79% vs 30%; P ¼ .0001) and secondary patency (93% vs 71%; P ¼ .03). 18 These comparisons demonstrate the advantage of using the FVT compared with prosthetic options as our primary patency was 65.9% at 1 year and 41.2% at 2 years, primary assisted patency was 95% at 1 year and 84.4% at 2 years, and secondary patency was 94.7% at 1 year and 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies showed lower primary patency rates with the HeRO graft, especially when a femoral vein transposition is used in the LEA, 2022 others found no significant difference. 23 Most studies showed similar results in terms of length of secondary patency, freedom from infection, and all-cause mortality.…”
Section: Discussionmentioning
confidence: 98%
“…A recomendação atual é que a fístula em membro superior seja a primeira escolha para o acesso permanente para hemodiálise 4 . No entanto, diante do desafio da impossibilidade do acesso em membros superiores, técnicas excepcionais podem ser utilizadas, como a transposição do veia braquial, a confecção de FAV no membro inferior autógena ou com prótese, entre outras [5][6][7][8][9][10][11] . A utilização de cateter de longa permanência em veia femoral só é indicada em pacientes com múltiplas comorbidades e baixa expectativa de vida 4 .…”
Section: Discussionunclassified